Characterization of a Novel Mannose-Binding Lectin with Antiviral Activities from Red Alga, Grateloupia chiangii - Hyun-Ju Hwang; Jin-Wook Han; Hancheol Jeon; Kichul Cho; Ju-hee Kim; Dae-Sung Lee; Jong Won Han (Biomolecules, 2020)
Lectins have the ability to bind specific carbohydrates and they have potential applications as medical and pharmacological agents. The unique structure and usefulness of red algal lectin have been reported, but these lectins are limited to a few marine algal groups. In this study, a novel mannose-binding lectin from Grateloupia chiangii (G. chiangii lectin, GCL) was purified using antiviral screens and affinity chromatography. We characterized the molecular weight, agglutination activity, hemagglutination activity, and heat stability of GCL. To determine the carbohydrate specificity, a glycan microarray was performed. GCL showed strong binding affinity for Maltohexaose-β-Sp1 and Maltoheptaose-β-Sp1 with weak affinity for other monosaccharides and preferred binding to high-mannan structures. The N-terminal sequence and peptide sequence of GCL were determined using an Edman degradation method and LC-MS/MS, and the cDNA and peptide sequences were deduced. GCL was shown to consist of 231 amino acids (24.9 kDa) and the N-terminus methionine was eliminated after translation. GCL possessed a tandem repeat structure of six domains, similar to the other red algal lectins. The mannose binding properties and tandem repeat structure of GCL may confer it the potential to act as an antiviral agent for protection against viral infection.